2011
DOI: 10.1111/j.1365-2966.2011.19421.x
|View full text |Cite
|
Sign up to set email alerts
|

Orbital effects of spatial variations of fundamental coupling constants

Abstract: We deal with the effects induced on the orbit of a test particle revolving around a central body by putative spatial variations of fundamental coupling constants $\zeta$. In particular, we assume a dipole gradient for $\zeta(\bds r)/\bar{\zeta}$ along a generic direction $\bds{\hat{k}}$ in space. We analytically work out the long-term variations of all the six standard Keplerian orbital elements parameterizing the orbit of a test particle in a gravitationally bound two-body system. It turns out that, apart fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…So far, this has been a motivator for astrophysical and cosmological studies beyond GR without including dark energy or dark matter, as it is used for explaining the present accelerating and expanding universe and other interesting problems in galaxies such as missing mass. It is well known that there is a highly significant indication that the temporal or spatial variations of physics constants reported have orbital effects [9,10]. Evidence for these effects motivates us to interpret other data in terms of spatial variation.…”
Section: Introductionmentioning
confidence: 93%
“…So far, this has been a motivator for astrophysical and cosmological studies beyond GR without including dark energy or dark matter, as it is used for explaining the present accelerating and expanding universe and other interesting problems in galaxies such as missing mass. It is well known that there is a highly significant indication that the temporal or spatial variations of physics constants reported have orbital effects [9,10]. Evidence for these effects motivates us to interpret other data in terms of spatial variation.…”
Section: Introductionmentioning
confidence: 93%
“…22,23 The orbital effects of the spatial variation of fundamental constants, the possibility of measurable influences of a variable speed of light, and violation of Lorenz symmetry have also been recently studied. [24][25][26] In parallel with these advances in the high precision measurement in cosmology, there are now extremely accurate databases of measurements for the distances in the inner solar system that date back to the early 70s of the past century. After the deployment of lunar ranging retroreflectors by the Apollo missions, it became possible to send laser beams to the Moon and detect the reflected beam at Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Dirac's argument and its implication on the Earth's evolution and temperature were discussed and constraints set onĠ/G [5,7,10]. Further experimental evidence suggested that G might present oscillations with period T G ≈ 6 yr [11] and induced new theoretical and experimental research to confirm and explain such a putative variation [12][13][14][15][16][17][18]. Data analyses are made difficult by the fact that, in Newton gravitation law, G is always found multiplied to the gravitational masses of the interacting bodies; but these masses are usually changing because of stellar wind and accretion from falling objects [19].…”
Section: Introductionmentioning
confidence: 99%